Clinical teaching in emergency medicine: the board round at Hope Hospital emergency department. Issue 9 (21st August 2007) - Carley, S; Morris, H; Kilroy, D
Abstract : This article discusses the educational value of the "board round", a clinical teaching forum introduced at Hope Hospital, Manchester, UK. At midday on weekdays all available consultants and middle grade doctors, and any other staff who can attend, meet to discuss a case selected from the patients currently in the department. As several experienced clinicians are available to discuss a clinical problem, the round allows a broad debate during which the merits of several management options are discussed. In addition, attending a board round addresses in part the concerns which senior clinicians may have about the balance of service delivery and protected teaching time. The paper describes several other advantages of this method of teaching, which has been adopted by other hospitals in the region.